DIDACTIC OPPORTUNITIES OF DUAL EDUCATION IN THE PROFESSIONAL TRAINING OF FUTURE EDUCATORS: ORGANIZATIONAL AND METHODOLOGICAL MECHANISMS (Web of Discoveries: Journal of Analysis and Inventions, 2026)
The contemporary landscape of teacher education in Uzbekistan is characterized by a persistent disconnect between the theoretical preparation of future educators and the practical demands of modern pedagogical environments. This article addresses the structural inefficiencies inherent in the conventional lecture-based model of pedagogical training and proposes dual education as a strategic didactic mechanism for transforming the quality of professional preparation of future educators. By integrating vocational education institutions, general education schools, and pedagogical research centers into a unified ecosystem of competency development, the dual education model aims to bridge the theory-practice divide, enhance graduate employability, and cultivate adaptive pedagogical competencies aligned with twenty-first century educational standards. The first part of this study critically analyzes the didactic foundations of dual education, drawing upon Dewey’s experiential learning theory and the competency-based education framework advanced by European qualification standards. It establishes the conceptual framework for shifting from a knowledge-transmission paradigm to a competency-formation paradigm in the professional training of educators.